Interleukin-33/ Suppression of Tumorigenicity 2 in Renal Fibrosis: Emerging Roles in Prognosis and Treatment - Tan, Xiao-Yang; Jing, Hao-Yue; Ma, Yue-Rong (Frontiers in Physiology, 2022)
Chronic kidney disease (CKD) is a major public health problem that affects more than 10% of the population worldwide and has a high mortality rate. Therefore, it is necessary to identify novel treatment strategies for CKD. Incidentally, renal fibrosis plays a central role in the progression of CKD to end-stage renal disease (ESRD). The activation of inflammatory pathways leads to the development of renal fibrosis. In fact, interleukin-33 (IL-33), a newly discovered member of the interleukin 1 (IL-1) cytokine family, is a crucial regulator of the inflammatory process. It exerts pro-inflammatory and pro-fibrotic effects via the suppression of tumorigenicity 2 (ST2) receptor, which, in turn, activates other inflammatory pathways. Although the role of this pathway in cardiac, pulmonary, and hepatic fibrotic diseases has been extensively studied, its precise role in renal fibrosis has not yet been completely elucidated. Recent studies have shown that a sustained activation of IL-33/ST2 pathway promotes the development of renal fibrosis. However, with prolonged research in this field, it is expected that the IL-33/ST2 pathway will be used as a diagnostic and prognostic tool for renal diseases. In addition, the IL-33/ST2 pathway seems to be a new target for the future treatment of CKD. Here, we review the mechanisms and potential applications of the IL-33/ST2 pathway in renal fibrosis; such that it can help clinicians and researchers to explore effective treatment options and develop novel medicines for CKD patients.